2015
DOI: 10.1371/journal.pone.0127508
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Catsper1 DNA Vaccine and Its Antifertility Effect on Male Mice

Abstract: Cation channel of sperm 1 (CATSPER1) is a unique sperm cation channel protein, and essential for sperm function and male fertility. CATSPER1 exclusively expresses in meiotic and postmeiotic spermatogenic cells, thus belongs to the spermatogenesis-specific antigen that escape central tolerance. We have previously demonstrated the immunocontraceptive potential of its transmembrane domains and pore region, and reported the antifertility effects of its B-cell epitopes on male mice. Aiming to develop DNA vaccine ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
4
11
0
Order By: Relevance
“…Previous studies have reported an apparent decrease in testis and epididymal weights, as well as obvious pathologic changes in the seminiferous tubules, of immunization animals . However, other studies have shown no pathological changes in the testis and epididymis . Our study was consistent with the latter.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Previous studies have reported an apparent decrease in testis and epididymal weights, as well as obvious pathologic changes in the seminiferous tubules, of immunization animals . However, other studies have shown no pathological changes in the testis and epididymis . Our study was consistent with the latter.…”
Section: Discussionsupporting
confidence: 92%
“…The fertility assays revealed that the mating fertility rates of the peptide group decreased significantly compared with the PBS group. The mechanism facilitating this decrease in fertility may be that peptides derived from ZNF185 induce specific antibody increases, which then enter the male reproductive tract through the serum and further suppress ZNF185 function . These results also validated our previous study, which indicated that ZNF185 is involved in spermatogenesis and male reproduction .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations